2012
DOI: 10.1371/journal.pone.0032454
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Natural Killer T Cell Agonist Modulates Experimental Focal and Segmental Glomerulosclerosis

Abstract: A growing body of evidence demonstrates a correlation between Th2 cytokines and the development of focal and segmental glomerulosclerosis (FSGS). Therefore, we hypothesized that GSL-1, a monoglycosylceramide from Sphingomonas ssp. with pro-Th1 activity on invariant Natural Killer T (iNKT) lymphocytes, could counterbalance the Th2 profile and modulate glomerulosclerosis. Using an adriamycin(ADM)-based model of FSGS, we found that BALB/c mice presented albuminuria and glomerular degeneration in association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In experimental models of lung diseases, Kimura et al (34) observed that the administration of αGalCer increased survival and reduced pulmonary fibrosis and TGF-β levels in the bleomycin model. In renal diseases, Pereira et al (35) found that GSL-1 (another NKT agonist) modulates the development of experimental focal and segmental glomerulosclerosis (EFSG) and, in the study by Mesnard et al (36), Jα18KO mice demonstrated worse renal function in anti-glomerular basement membrane (anti-GBM) glomerulonephritis. These data support our findings that Jα18 knockout mice are prone to a higher percentage of fibrosis and that administration of αGalCer was effective in reducing this process.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models of lung diseases, Kimura et al (34) observed that the administration of αGalCer increased survival and reduced pulmonary fibrosis and TGF-β levels in the bleomycin model. In renal diseases, Pereira et al (35) found that GSL-1 (another NKT agonist) modulates the development of experimental focal and segmental glomerulosclerosis (EFSG) and, in the study by Mesnard et al (36), Jα18KO mice demonstrated worse renal function in anti-glomerular basement membrane (anti-GBM) glomerulonephritis. These data support our findings that Jα18 knockout mice are prone to a higher percentage of fibrosis and that administration of αGalCer was effective in reducing this process.…”
Section: Discussionmentioning
confidence: 99%
“…In the balb/c mouse background, a 10 mg/kg dose of ADM was injected to induce the disease (Pereira et al, 2011; Pereira et al, 2012). In the C57black/6 strain, a higher dose of 25 mg/kg ADM was used (Jeansson et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The immunological mechanisms involved in the pathogenesis of FSGS are unclear, but evidence suggests an association between Th2-polarization and disease development [ 50 ]. For example, Yap et al reported a correlation between childhood idiopathic nephrotic syndrome and increased IL-13 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%